4D printing light-/thermo-responsive shape memory composites based on thermoplastic polyurethane/polylactic acid/polyaniline blends. (May 2023) - Wang, Yanmei; Wang, Yanen; Liu, Minyan; Wei, Qinghua; Du, Bing
In this work, a series of polylactic acid/thermoplastic polyurethane/polyaniline (PLA/TPU/PANI) blends with different weight ratios were prepared by Fused deposition molding First, six groups of PLA/TPU (U9A1/U8A2/U7A3/U6A4/U5A5/U4A6) and three groups of PLA/TPU/PANI (821/823/825) with different ratios were fabricated by melt blending. Then, the effects of different filament forming and printing process parameters on print resolution and quality were investigated. Next, printed samples were characterized by Fourier transform infrared (FTIR), Thermogravimetric analysis (TGA), Scanning electron microscopy (SEM) and mechanical experiments. The results of FTIR and TGA showed no chemical reaction between different components, and uniform distribution of the material was observed in the SEM. The tensile and compressive curves of the samples showed an inverted U-shape. Finally, the shape-memory property was evaluated by differential scanning calorimetry. For PLA/TPU blends, U8A2 had the best shape memory capability (R r = 80.8% andR f = 100%). Based on the excellent shape memory performance of PLA/TPU, the addition of PANI can introduce a light-actuated mechanism to form a binary-driven shape memory material. The composite materials prepared in this work can be applied to tissue engineering scaffolds, medical devices, soft robots and so on. Graphical Abstract